To rewrite the equation \(-4X + 3 = 10\) in two equations joined by "and," we can break it down into two parts:
-
Isolate the term involving \(X\): \[ -4X + 3 = 10 \] Subtract 3 from both sides: \[ -4X = 7 \]
-
Divide both sides by -4 to solve for \(X\): \[ X = -\frac{7}{4} \]
Now we can express the original equation as two equations:
-
The equation itself: \[ -4X + 3 = 10 \]
-
The solution found: \[ X = -\frac{7}{4} \]
Thus, we can write it as:
\[ -4X + 3 = 10 \quad \text{AND} \quad X = -\frac{7}{4} \]
If you meant to join them in a different way or have additional context to consider, please clarify!